Perlindungan Hutan Amazon Berdasarkan Konvensi UNFCCC (United Nations Framework Convention On Climate Change) - Aponno, Frederika; Hanafi, Irma Halima; Riry, Welly Angela (PATTIMURA Law Study Review, 2025)
: In recent years, forests have become rare due to human activities. The decreasing number of trees has an impact on the forest's ability to absorb pollution in the air. Deforestation is the main cause of forest destruction. Forest protection in this modern era is becoming increasingly important because forests have a very large role in maintaining the balance of the global environment, providing important ecosystem services, including absorbing carbon dioxide as previously explained. Raising the issue of forest protection as a global agenda is a strategic effort to increase awareness and global cooperation in stopping the rate of forest destruction. Various global forums under the United Nations (UN) have supported the implementation of sustainable forest management (Sustainable Forest Management/SFM) at the national, regional and international levels. The research method used in researching and discussing this problem is normative juridical which uses a legislative approach and a conceptual approach. The legal materials used are primary, secondary and tertiary legal materials. The results of this study emphasize that there is a need for closer international cooperation, both between countries that have the Amazon Forest and with donor countries, to increase funding and technology in conservation efforts. Then it is important to increase public education and awareness about the importance of the Amazon Forest, so that it can involve local communities in efforts to protect and manage forest resources. In addition, it is hoped that the UN can ensure that forest protection is integrated into national and local development plans, so that there is no conflict between economic development and environmental conservation.